2013
DOI: 10.1111/ropr.12009
|View full text |Cite
|
Sign up to set email alerts
|

Media Framing and Public Attitudes Toward Biofuels

Abstract: This study investigates the relationship between media framing and public opinion on the issue of biofuels-transportation fuels made from plants, animal products, or organic waste. First, the paper investigates how media framing of biofuels has changed since the issue regained national prominence in the early 2000s. Through a detailed content analysis of newspaper coverage, the paper documents an increase in negative frames between 1999 and 2008, especially frames focusing on the negative economic effects of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 28 publications
2
43
0
1
Order By: Relevance
“…Framing effects research related to public attitudes toward biofuel policy options suggests that public opinion is complex and that nuances of language may play a role in public deliberation and decision-making [26]. Framing research has evolved over the past 40 years from its multidisciplinary roots in sociology, psychology, behavioral economics, and linguistics across a broadly applied conceptual territory [27].…”
Section: Framingmentioning
confidence: 99%
“…Framing effects research related to public attitudes toward biofuel policy options suggests that public opinion is complex and that nuances of language may play a role in public deliberation and decision-making [26]. Framing research has evolved over the past 40 years from its multidisciplinary roots in sociology, psychology, behavioral economics, and linguistics across a broadly applied conceptual territory [27].…”
Section: Framingmentioning
confidence: 99%
“…That of Delshad and Raymond (2013) confirmed that public attitudes appear to be shaped by new media frames, especially among those who indicated a high degree of attention to the media. Other important factors that can influence public opinion on biofuel issues include regional economic interests, partisanship and ideology.…”
Section: Knowledge Attitude and Perceptions On Biofuel Productionmentioning
confidence: 66%
“…Other studies have investigated recent changes in media framing of biofuels and their possible effect on public attitudes towards different biofuels technologies and policies (Chang, 2009;Delshad and Raymond, 2013). That of Delshad and Raymond (2013) confirmed that public attitudes appear to be shaped by new media frames, especially among those who indicated a high degree of attention to the media.…”
Section: Knowledge Attitude and Perceptions On Biofuel Productionmentioning
confidence: 81%
“…As we argue below, however, public attitudes towards biofuels in both the United States and Canada are based on relatively low levels of information about the technology, and are therefore relatively weak and subject to change [6]. Indeed, other work has shown that while U.S. consumers' attitudes towards corn-based ethanol were initially positive, support declined over time as the potential economic, social, and environmental costs of the technology were pointed out by those opposed to biofuels policies [10,12]. It is possible, then, that as North American consumers become more familiar with cellulosic ethanol and are exposed to arguments that oppose its widespread adoption, approval for this type of biofuel could also decline in the coming years, which could threaten the future of the biofuels industry in North America.…”
Section: Introductionmentioning
confidence: 88%
“…American consumers, moreover, have a clear preference for second-generation biofuels over corn-based ethanol [7], showing, for example, a greater willingness-to-pay (WTP) a premium for an E85 fuel blend produced from switchgrass than for corn-based E10 [8] and a small but significant preference for wood-based over corn-based ethanol [9]. Indeed, while Delshad and Raymond [10] found weak support for policies promoting biofuels production in their sample of respondents, the one exception was a subsidy for producers of cellulosic biofuels, which received 67% support. Overall, then, evidence from U.S. consumer attitudes provides a testable hypothesis in the Canadian context: H1 (corn): Canadians will prefer biofuels produced from feedstocks other than corn over corn-based ethanol.…”
Section: Preference For Non-corn Feedstocks Over Corn-based Ethanolmentioning
confidence: 96%